Chemomechanical interplay of layered cathode materials undergoing fast charging in lithium batteries. (November 2018) - Xia, Sihao; Mu, Linqin; Xu, Zhengrui; Wang, Junyang; Wei, Chenxi; Liu, Lei; Pianetta, Piero; Zhao, Kejie; Yu, Xiqian; Lin, Feng; Liu, Yijin
Abstract: Morphological defects contribute to chronic and acute failures of batteries. The development of these morphological defects entails the multiscale chemo-mechanical coupling associated with internal mechanical stress. The mechanical stress, caused by anisotropic structural, chemical and state of charge (SOC) heterogeneities, is released through crack formation, undermining the continuous diffusion pathways of electrons and ions and creating fresh surfaces for electrode–electrolyte side reactions. The understanding of chemomechanical interplay has remained at the descriptive level, thus, the quantification or model to fingerprint these processes is highly desired. Herein, we systematically investigate the mesoscale morphological defects within LiNi0.6 Mn0.2 Co0.2 O2 secondary particles that have gone through fast-charging conditions. With the advanced synchrotron X-ray tomography, we nondestructively pierce the internal volume of secondary particles and quantify the morphological outcomes of the crack formation, such as porosity and internal surface area. We then develop a numerical model to predict the crack-induced diffusion deterrent of electrons and lithium ions. The mismatch between the local ionic and electronic conductivity can lead to highly heterogeneous SOC distribution in secondary particles, which exponentially deteriorates as the current density increases. Our incisive investigation of chemomechanical interplay and fast-charging can inform a knowledge base to accelerate the discovery of advanced materials that are resilient against chemomechanical failures. Graphical abstract: fx1 Highlights: The mesoscale morphological defects in LiNi0.6 Mn0.2 Co0.2 O2 secondary particles are systematically studied. Numerical model is built to predict the crack-induced diffusion deterrent of electrons and lithium ions. Infiltration of electrolyte causes mismatch between the local ionic and electronic conductivity. Heterogeneity of the local current density over the particle surface further contributes to the capacity fade.